The Impact of Teachers' Classroom Management Skills on Students' Interest in Learning The English Subject: English - Imam Sagita; Mudiyono (Prodi Tadris Bahasa Inggris, 2023)
Teachers are expected to possess a diverse range of skills and qualities, including personal, scientific, technical, social, and spiritual proficiencies, all crucial for their profession. This encompasses expertise in their subject matter, understanding of students' needs, fostering educational growth, and continuous self-development alongside professional advancement. This study aims to evaluate how teachers' ability to manage their classrooms impacts students' enthusiasm for learning, using a quantitative method, specifically a correlational approach. Data was gathered through questionnaires and documentation, utilizing a Likert scale to assess teacher competencies, classroom management, and student interest in learning. The research focused on fourth-grade students at MI NU Sumber Agung, employing cluster sampling to select participants. Statistical analysis indicated a significant influence, with F. count > F. table (15.886 > 3.30). These results confirm that both teacher competence and effective classroom management play vital roles in shaping the learning enthusiasm of fourth-grade students at MI NU Sumber Agung.